(untitled) (Research, Society and Development, 2023)
Introduction: One of the surgical wound complications is scarring dehiscence, which generates clinical and socioeconomic impact. Coadjuvant therapies such as (O3) therapy, ozone therapy, have been widely used in clinical practice and show promising results in the context of skin wounds. Objective: The purpose of this study is to present, through a narrative review, an understanding of the available evidence regarding the importance of ozone therapy in skin repair and possible applicability in the treatment of cicatricial dehiscence. Methods: The bibliographic databases of PubMed/MEDLINE, Virtual Health Library (VHL), Web of Science and SciELO were used. Results: Of the 159 identified articles, 13 eligible articles were established to evaluate the effect of O3 on skin repair. Evidence shows that ozone therapy can be considered an effective strategy in enhancing skin repair, such as acute and chronic skin wounds, as it modulates the inflammatory process, helps the proliferation of cells responsible for skin repair, increases the expression of factors responsible for the formation of components of the extracellular matrix, improves vascularization with consequent optimization of granulation tissue formation and wound closure. Conclusion: In this way, the findings of the study direct that ozone therapy could be proposed as a promising therapeutic strategy in the treatment of cicatricial dehiscence, justified due to the positive effects in the repair of cutaneous and acute and chronic wounds. However, experimental studies and clinical trials are needed to endorse its safety and dosimetric efficacy in the treatment of cicatricial dehiscence.